The Therapy of Desire in Times of Crisis: Lessons Learned from Buddhism and Stoicism - Xiaojun Ding; Yueyao Ma; Feng Yu; Lily M. Abadal (Religions, 2023)
Desire is an important philosophical topic that deeply impacts everyday life. Philosophical practice is an emerging trend that uses philosophical theories and methods as a guide to living a eudaimonic life. In this paper, we define desire philosophically and compare different theories of desire in specific Eastern and Western traditions. Based on the Lacanian conceptual–terminological triad of “Need-Demand-Desire”, the research of desire is further divided into three dimensions, namely, the subject of desire, the object of desire, and the desire itself. The concept of desire is then analyzed from this triad and these three dimensions through different philosophical theories. This paper selects Buddhism as the representative of Eastern tradition, and Stoicism as the representative of the West, paying special attention to Stoicism’s “spiritual exercises” following Pierre Hadot. By exploring and comparing the Buddhist paths to liberation from suffering (i.e., the Four Noble Truths and the Noble Eightfold Path) and the two theoretical pillars in Stoicism (i.e., the notions of “living according to nature” and “the dichotomy of control”), practical guidance is then provided for understanding and regulating desire in times of crisis. This understanding and regulation of desire constitutes a philosophical therapy for today’s troubles, particularly those caused by excessive or irrational desires.